Impact of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Vaccination and Pediatric Age on Delta Variant Household Transmission. (22nd March 2022) - Ng, Oon Tek; Koh, Vanessa; Chiew, Calvin J; Marimuthu, Kalisvar; Thevasagayam, Natascha May; Mak, Tze Minn; Chua, Joon Kiat; Ong, Shannen Si Hui; Lim, Yong Kai; Ferdous, Zannatul; Johari, Alifa Khairunnisa bte; Cui, Lin; et al.
Abstract: Background: In Singapore, quarantine of all close contacts with entry and exit polymerase chain reaction testing enabled evaluation of the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination and pediatric age on transmission of the Delta variant. Methods: This retrospective cohort study included all household close contacts between 1 March 2021 and 31 August 2021. Results: Among 8470 Delta variant-exposed contacts linked to 2583 indices, full-vaccination of the index with BNT162b2 or mRNA-1273 was associated with reduction in acquisition by contacts (adjusted odds ratio [aOR], 0.56; 95% robust confidence interval [RCI], .44–.71 and aOR, 0.51; 95% RCI, .27–.96, respectively). Compared with young adults (aged 18–29 years), children (aged 0–11 years) were significantly more likely to transmit (aOR, 2.37; 95% RCI, 1.57–3.60) and acquire (aOR, 1.43; 95% RCI, 1.07–1.93) infection, vaccination considered. Longer duration from vaccination completion among contacts was associated with decline in protection against acquisition (first-month aOR, 0.42; 95% RCI, .33–.55; fifth-month aOR, 0.84; 95% RCI, .55–.98; P < .0001 for trend) and symptomatic disease (first-month aOR, 0.30; 95% RCI, .23–.41; fifth-month aOR, 0.62; 95% RCI, .38–1.02; P < .0001 for trend). Contacts immunized with mRNA-1273 had significant reduction in acquisition (aOR, 0.73; 95% RCI, .58–.91) compared with BNT162b2. Conclusions: Among household close contacts, vaccination prevented onward SARS-CoV-2 transmission and there was increased risk of SARS-CoV-2 acquisition and transmission among children compared with young adults. Time after completion of vaccination and vaccine type affected SARS-CoV-2 acquisition. Abstract : Among 8470 Delta-exposed household close contacts, vaccination prevented onward severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission. There was increased risk of SARS-CoV-2 acquisition and transmission among children compared with young adults. Time after vaccination and vaccine type affected acquisition.